1999
DOI: 10.1094/phyto.1999.89.9.831
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Distribution and Temporal Development of Fusarium Crown and Root Rot of Tomato and Pathogen Dissemination in Field Soil

Abstract: The spatial distribution and temporal development of tomato crown and root rot, caused by Fusarium oxysporum f. sp. radicis-lycopersici, were studied in naturally infested fields in 1996 and 1997. Disease progression fit a logistic model better than a monomolecular one. Geostatistical analyses and semivariogram calculations revealed that the disease spreads from infected plants to a distance of 1.1 to 4.4 m during the growing season. By using a chlorate-resistant nitrate nonutilizing (nit) mutant of F. oxyspor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
60
0
5

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(65 citation statements)
references
References 25 publications
0
60
0
5
Order By: Relevance
“…Distances between roots were smallest in the zone of highest root density (2-4 cm below stem plates) and roots frequently extended horizontally in this zone, providing a direct route for mycelial growth to other plants. Rekah et al (1999) reported that tomato roots seemed to be essential for movement of the fusarium crown rot and root rot pathogen in soil, and therefore may be regarded as tubes filled with a highly selective and rich habitat protecting the colonising pathogen from the activity of antagonistic micro-organisms. In the CCS pathosystem, the carrot root system was modelled as a single cylinder and possible infections of radicles on the same plant via the taproot were initially ignored (Suffert, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Distances between roots were smallest in the zone of highest root density (2-4 cm below stem plates) and roots frequently extended horizontally in this zone, providing a direct route for mycelial growth to other plants. Rekah et al (1999) reported that tomato roots seemed to be essential for movement of the fusarium crown rot and root rot pathogen in soil, and therefore may be regarded as tubes filled with a highly selective and rich habitat protecting the colonising pathogen from the activity of antagonistic micro-organisms. In the CCS pathosystem, the carrot root system was modelled as a single cylinder and possible infections of radicles on the same plant via the taproot were initially ignored (Suffert, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…radicis-lycopersici (Rekah et al ., 1999(Rekah et al ., , 2001, pea root rot due to Aphanomyces euteiches (Pfender & Hagedorn, 1983), wheat take-all due to Gaeumannomyces graminis var. tritici (Colbach et al ., 1997;Bailey & Gilligan, 1999), and diseases caused by Phytophthora parasitica var.…”
Section: Introductionmentioning
confidence: 99%
“…Com o diagnóstico sobre a capacidade de dispersão da doença no campo, é concebível o desenvolvimento de programas eficientes de controle da doença na cultura e para outros patógenos com mecanismos semelhantes ao da fusariose no cultivo da pimenta-do-reino (REKAH et al, 1999;IKEDA, 2010).…”
Section: II Ii I Sunclassified
“…Pathogen attacks result in the development of symptoms that include leaf and fruit wilt, stem and root rot (Rekah et al, 1999), coverage of leaf surface with pustule, chlorosis and necrosis (Fofana et al, 2007, Kocal et al, 2008 (Figure 2), a decreased rate of plant photosynthesis (Kocal et al, 2008), and as a consequence plant death or yield loss ensues (Berger et al, 2007). Fig.…”
Section: For the Plantmentioning
confidence: 99%